Biological and Phylogenetic Analyses, Evidencing the Presence of Gnomoniopsis Sp. in India, Causing Canker of Chestnut Trees: a New Report - Dar, Mudasir A.; Rai, Mahendra (Indian Forester, 2013)
In India the chestnut population is confined to the Northern part of the country particularly in Jammu and Kashmir. Twenty seven isolate of genus Gnomoniopsis were recovered in pure culture from infected chest nut trees growing in different places of Jammu and Kashmir. The morphological characteristics and the phylogeny of these isolates proved it to be Gnomoniopsis. The molecular identification of the isolates was carried out by rDNA based ITS markers, using ITS1, 5.8s and ITS2 for amplification and these rDNA regions were used to define the isolates as Gnomoniopsis. It is a first report of occurrence of Gnomoniopsis sp. from India.